ANALISIS PENGARUH E-CUSTOMER RELATIONSHIP MANAGEMENT (E-CRM) DAN E-SERVICE QUALITY TERHADAP E-LOYALTY DENGAN E-WOM SEBAGAI VARIABEL INTERVENING (Studi pada Pengguna Aplikasi MAPCLUB di Kota Semarang) - Berliana Cahyaran; Sri Rahayu Tri Astuti (Diponegoro Journal of Management, 2022)
As technology develops, people's lifestyles also change. One of the most visible changes is people's spending patterns. Currently, there are many online shopping sites, one of which is MAPCLUB which provides a variety of fashion needs. However, in the MAPCLUB application, there are differences in ratings and the appearance of reviews about the application which causes doubts in using the application. This study aims to analyze the effect of the relationship between E-CRM, E-Service Quality on E-Loyalty with the role of E-WOM as an intervening variable on MAPCLUB application users in Semarang City. The number of samples used in this study was 108 respondents with the criteria of respondents are domiciled in the city of Semarang, aged at least 17 years, have made repeated purchases on the MAPCLUB application at least 2 times, and are active users of the MAPCLUB application at least in the last 6 months. This research was conducted using quantitative methods and SEM analysis methods with AMOS as a data processing tool. The results showed that E-CRM, E-Service Quality, and E-WOM had a positive and significant effect on E-Loyalty.